(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Rocket propulsion systems, long-distance transportation, and the long-term storage of vast quantities of frozen food all depend on cryoliquids. Cryoliquids are notoriously difficult to transport and store since they boil at a temperature below absolute zero. The expansion rates of these low-temperature liquids may reach 700 times, thus additional safety precautions must be included in the pipelines or storage facilities that house them. Pipes may rupture if internal pressure rises over safe thresholds. At this point, the significance of the safety pressure release valve becomes evident. When the thermal relief valve reaches a certain pressure, it will open to release pressure from the section and then shut to return to its starting position.